2020
DOI: 10.1002/chem.201903985
|View full text |Cite
|
Sign up to set email alerts
|

Reversible Phase Transition of Porous Coordination Polymers

Abstract: Porous coordination polymers or metal–organic frameworks with reversible phase‐transition behavior possess some attractive properties, and can respond to external stimuli, including physical and chemical stimuli, in a dynamic fashion. Their phase transitions can be triggered by adsorption/desorption of guest molecules, temperature changes, high pressure, light irradiation, and electric fields; these mainly include two types of transitions: crystal–amorphous and crystal–crystal transitions. These types of porou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(19 citation statements)
references
References 111 publications
1
17
0
Order By: Relevance
“…It should be mentioned that this process is reversible and intercalated solvent can penetrate and introduce the other phase formation. Similarly, such solvent stimulus response studies on MOF were performed previously on Zn-, Cd-and other metal-based MOFs [59][60][61]. With DCM and methanol, a broadening of the peak (001) was observed due to the loss in crystallinity (Figure 4, curves d and f).…”
Section: Resultssupporting
confidence: 55%
“…It should be mentioned that this process is reversible and intercalated solvent can penetrate and introduce the other phase formation. Similarly, such solvent stimulus response studies on MOF were performed previously on Zn-, Cd-and other metal-based MOFs [59][60][61]. With DCM and methanol, a broadening of the peak (001) was observed due to the loss in crystallinity (Figure 4, curves d and f).…”
Section: Resultssupporting
confidence: 55%
“…Generally, for a certain experimental condition, only one polymorphic phase of an assigned molecular formula is thermodynamically stable, as all other phases are metastable. Since the structural arrangement can determine the physicochemical properties of crystalline materials but is often difficult to control, polymorphism has long been considered as a huge challenge to be studied and recognized. Faced with this, the approach toward polymorphism (or phase) has continually been changing because of advances made in controlling the synthesis of the target polymorphs rather than it being a metastable in some specific systems. In both organic and inorganic systems, they can form different polymorphs owing to the weak and/or nondirectional intermolecular interactions, like hydrogen bonds, π–π stacking, van der Waals, S–S, S–N, and S–C interactions, etc .…”
Section: Introductionmentioning
confidence: 99%
“…[5,6] Intense research efforts have shown that macroscopic parameters such as topology, [7,8] dispersion interactions and vibrational entropy [9][10][11][12] as determined by microscopic chemical interactions all contribute to structural flexibility; however, the targeted synthesis of flexible MOFs which concerns the manipulation of macroscopic thermodynamics via chemical changes on a microscopic level is still beyond our knowledge. Therefore, it is not surprising that the number of flexible MOFs [13][14][15][16] is still small when compared to the total number of existing MOFs, [17] with MOFs such as ZIF-4(Zn) (zeolitic imidazolate framework, Zn(im) 2 , with im À = imidazolate) [18][19][20] and M(bdp) (M 2+ = Fe 2+ or Co 2+ , bdp 2À = 1,4-benzenedipyrazolate) [21,22] being two of several important examples that show large structure flexibility as a function of varying temperature and (gas) pressure.…”
Section: Introductionmentioning
confidence: 99%